Routine Testing for Every Pregnant Patient Between 32 Weeks of Gestation for Early Diagnosis of Gestational Hypertension (Roll Over Test) in Third Trimester Pregnant Women - Nur Rahma Srifitayani; Cakrawati R Cakrawati R (International Journal of Health Sciences, 2026)
ABSTRACT Gestational hypertension is a pregnancy complication that can increase the risk of maternal and fetal morbidity and mortality. Early detection of gestational hypertension is crucial to prevent the development of preeclampsia and other pregnancy complications. One screening method that can be used is the Roll Over Test ( ROT) , which is performed at approximately 28–32 weeks of gestation. This study aims to analyze the effectiveness of routine Roll Over Tests at 32 weeks of gestation in early detection of gestational hypertension in pregnant women in the third trimester . The study used a quantitative approach with a descriptive analytical design. The sample consisted of 40 pregnant women in their third trimester undergoing antenatal care. Data were collected through blood pressure measurements using the Rolling Test method and observations of pregnancy conditions. Data were analyzed univariately and bivariately using the Chi- Square test . The results showed that 30% of respondents had a positive Rollover Test result. The analysis showed a significant association between a positive Rollover Test result and the incidence of gestational hypertension (p = 0.003). Routine check-ups at 32 weeks of gestation can help identify pregnant women at risk of developing gestational hypertension early . Keywords: Gestational Hypertension , Rolling Test, Third Trimester Pregnancy , Pregnancy Screening, Antenatal Care